Mad hazard : a life in social theory - Turner, Stephen P., 1951- (Current perspectives in social theory ;, 2022)
Mad Hazard is a memoir of the career and life of Stephen Turner, chronicling a life in social theory. Showcasing how Turner's later work on expertise, tacit knowledge, cognitive science, leadership, and liberal democracy developed out of his early interests, this volume describes the institutional and personal constraints and pressures, as well as the personal relationships, that facilitated and shaped an academic career. From Turner's childhood in the racially violent South Side of Chicago, the development of his interests in social theory, through to his education in the shadow of the war in Vietnam and a period of social and personal turmoil, this biographical work shows us not only the development of academic thinking, but the evolution of an academic career. The rebellion within sociology against the hegemonic Merton-Parsons conception of sociology and the methodological orthodoxies of the time leads through to a discussion of the philosophy of science and social science, and from there to a reassessment of the inherited view of the classics, to science studies, and to political and international relations theory - the comprehensive nature of Mad Hazard means the reader can truly understand how Turner's academic journey evolved. Revealing an academic career not dependent on prestige and academic power, but also not untouched by hierarchy and academic politics, Mad Hazard is appealing for readers interested in the field of social theory, and beyond that, those interested in the evolution of intellectual life in the present university.